Clinical pharmacokinetics of methotrexate in oncology. (May 2017) - Levêque, Dominique; Becker, Guillaume; Toussaint, Elise; Fornecker, Luc-Matthieu; Paillard, Catherine
Methotrexate is an antifolate agent used in the treatment of autoimmune diseases and various types of cancers. It is a unique antiproliferative agent because it can be administered by multiple routes with a wide variation of dosing. Methotrexate pharmacokinetics have generated numerous papers focusing on descriptive data and pharmacodynamics. Methotrexate is one of the rare anticancer agents which pharmacokinetics are routinely monitoring to control excessive toxicity when administrated at high dose (>1 g/m 2 ). The identification of transporters involved in its disposition has permitted the understanding and the prevention of most drug interactions. Pharmacogenetic factors affecting the expression of MRP2 and OATP1B1 partly explain the interindividual variability of methotrexate clearance. The remaining challenge in methotrexate pharmacokinetics is to further understand unexplained delayed renal elimination despite the implementation of preventive measures.